Distal Radius Malunion and Forearm Rotation: A Cadaveric Study - Bronstein, Andrew; Heaton, Dennis; Tencer, Allan F.; Trumble, Thomas E. (Journal of Wrist Surgery, 2014)
Background Malunions following distal radius fractures are common, with shortening, translation, and rotation occurring. The patients frequently lose forearm rotation, but there is no data to indicate whether this is due to mechanical misalignment between the radius and the ulna or to contracture of the soft tissues.Material and Methods Seven fresh cadaveric specimens were used to determine the loss of forearm rotation with varying simulated distal radius fracture malalignment patterns. Uniplanar malunion patterns consisting of dorsal tilt, radioulnar translation, or radial shortening were simulated by creating an osteotomy at the distal end of the radius.Description of Technique By orienting the distal fragment position using an external fixator and maintaining the position with wedges and a T-plate, varying degrees of malunion of the distal radius could be simulated. Rotation of the forearm was produced by fixing the elbow in a flexed position and applying a constant torque to the forearm using deadweights. Forearm rotation was measured with a protractor.Results Dorsal tilt to 30° and radial translation to 10 mm led to no significant restriction in forearm pronation or supination ranges of motion. A 5-mm ulnar translation deformity resulted in a mean 23% loss of pronation range of motion. Radial shortening of 10 mm reduced forearm pronation by 47% and supination by 29%.Conclusion Because a severe osseous misalignment was required to produce a significant loss in rotation, contracture of the soft tissues is most likely the cause of the loss of rotation in most cases.
Keywords: allograft; artilage; thumb arthritis; ligament; stability